(untitled) (Molecular Medicine Communications, 2023)
Osteoporosis is a critical and complicated systemic musculoskeletal disorder that encompasses low bone density (LBD) and weakening of osseous tissue at a microarchitectural level. This predisposes to increased bone fragility and subsequent risk of fractures. It is frequently encountered in postmenopausal women and has also been seen in elderly men. Vitamin D synchronizes bone and calcium homeostasis in the body by modifying the transcription of target genes through the Vitamin D receptor (VDR) and thus aids calcium uptake and bone-forming proteins. The main objective of the present research was to study the relationship of single nucleotide polymorphisms (SNP) (rs1544410 G>A) of the VDR gene with postmenopausal women who have osteoporosis in a Pakistani cohort. A total of 100 postmenopausal women, 50 without osteoporosis to be in the control group, and 50 with osteoporosis as cases, were enrolled in this study. The patients had no immediate family connections with each other. All the patients underwent BMD measurements at the lumbar spine and femoral neck by dual-energy X-ray absorptiometry scan for their diagnosis of osteoporosis based on World Health Organization (WHO) criteria (T score < -2.5 SD). A total of 25 participants had at least one allele of rs1544410, of which 14 were cases and 11 controls. The number of heterozygous and homozygous were present with similar ratios in both groups (p=0.973). Age was noted to be correlated with osteoporosis (OR: 1.06; 95%CI: 1.004-1.12), (P<0.031). It was also observed that cases had a notably lower weight than the control group (P<0.0001) and the overall body mass index of cases was significantly low in comparison to control (P<0.0001). Moreover, average BMD of femoral and BMD lumbar were notably greater among the control group (P<0.0001) as compared to cases. The SNP (rs1544410) is not significantly associated with BMD but significantly correlated with age which was identified as a risk factor while body mass index was found to be a protective factor for osteoporosis